Deteksi Anemia dan Thalasemia di Panti Asuhan Putri Muhammadiyah Purwokerto - Noviyana, Alfi; Purwati, Purwati (Universitas Respati Yogyakarta, 2019)
Anemia in adolescents is a public health problem because it can reduce the quality of human resources. The almost identical clinical picture of anemia and thalassemia makes thalassemia escape detection. The Objectives of this activity are increase partner knowledge about anemia in adolescents and screening for thalassemia, in addition to overcoming existing problems so that partners can maintain their health, can enter a family life with healthy reproduction. The method used by giving IEC (Communication, Information, Education) to partners regarding anemia and thalassemia. This IEC is in the form of counseling and health education as well as problem solving training. The result of this program activities are carried out in accordance with the plan and succeed with consistent participant indicators from the beginning to the end of the program, increased insight and knowledge of partners can be seen from the accuracy in understanding the material, modules and leaflets that provided. Conclusion are knowledge and skills partners about anemia and thalassemia increased.Keywords: anemia, thalassemia, adolescents